PERKEMBANGAN MUATAN HAM DALAM KONSTITUSI DI INDONESIA - Muhammad Amin Putra (Universitas Lampung, 2015)
Briefly Human Rights can be divided into three categories, including: first, the first generation of Human Rights of a matter of civil rights and politics, secondly, about the rights of economic, social and cultural, and the third, representing the right to equality. Enforceability constitution in Indonesia including of the Constitution RIS of 1949 and Provisional Constitution RIS 1950, the Constitution of 1945, Amendment (I-IV) of the 1945 Constitution. Enforceability of human rights in the constitution in Indonesia has a different history in terms of the setting and the mention. Contents of Human Rights not only based on the rights of association, assembly, and contend yet more extensive and specific. The charge of human rights in the 1945 Constitution Amendment 1-4 nearly includes all the settings of the Universal Declaration in 1948.Keywords: Human Rights, Constitution, Law